# How do you solve the following system?: #-x -2y =1, 9x -y = -1#

##### 1 Answer

Nov 14, 2015

#### Answer:

We can solve this question by finding the value of x with respect to y from both equations. Since the value of x should be equal, the equations thus obtained can be solved for y. And then either of the initial equations can be used to find x.

#### Explanation:

#-x-2y# = 1 =>#-x=1+2y# =>#x=-(1+2y)# ----EQUATION 1#9x-y=-1# =>#9x=y-1# =>#x=1/9*(y-1)# ----EQUATION 2

Equating the values of x from EQUATION 1 and EQUATION 2;

we have;

=>

=>

=>

=>

Using EQUATION 1;

=>

=>

=>

So there you have it!!

and